Standardized classification of mechanical ocular injuries: Efficacy and shortfalls - Doğramacı, Mahmut; Karaman Erdur, Sevil; Şentürk, Fevzi (My University, 2021)
Objectives: The aim of this study was to examine the efficacy and the shortfalls of the Birmingham Eye Trauma Terminology classification system for ocular trauma in predicting the visual outcome. Methods: The records of 256 eyes of 246 patients with a diagnosis of mechanical ocular trauma admitted to the Osman Gazi University Hospital ophthalmology department between 1995 and 2000 were retrospectively reviewed. The zone, type, grade, and pupil status of the injuries were determined according to the Birmingham classification system. Injuries with a good prognosis were defined as injuries that resulted in vision of equal to or better than counting fingers at 1 meter. Fischer’s exact test was used to determine the statistical significance of relationships between the final visual acuity and the initial clinical findings. Results: Open eye injuries restricted to zone I, those with no afferent pupillary defect, and those graded as 3 or better or classed as type B were significantly associated with a better visual outcome (p<0.05). Open eye injuries that extended to zone III, had an afferent pupillary defect, or were graded as 4 or worse were significantly associated with a poorer visual outcome (p<0.05). Closed eye injuries classified as type B or grade 4 were significantly associated with a poor visual outcome (p<0.05). Conclusion: The Birmingham classification system for mechanical ocular trauma offers a standardized method for both open and closed eye injuries, however, adding subclasses to type C (injuries with foreign body involvement) could enhance the classification method and help to understand the influence of foreign body properties and sizes on the outcome.
Keywords: Birmingham Classification; Classification; Mechanical Trauma